High Yield Production of Industrially Important Multi Enzymes by Aspergillus Foetidus using Solid State Fermentation - S, Ashwini; M.P, Raghavendra (Asian Journal of Biological and Life Sciences, 2016)
Isolation and screening of Aspergillus foetidus strains for the biosynthesis of high yield multi enzymes such as amylase, protease, xylanase and pectinase was conducted using solid state fermentation wherein agrowaste rice and wheat bran was used as a fermentation substrate. Different fermentation parameters were evaluated for maximum enzymes production. The results revealed that highly significant enzyme secretion was observed in rice bran substrate with optimum temperature 28°C, pH 4-6, 40% moisture content, 0.2ml inoculum size (24 million spores/gram) and 48 hrs. of incubation period. Under these fermentation parameters maximum enzyme activity for amylase (9,145 U/g), protease (2,013 U/g), xylanase (14,641U/g) and pectinase (390 U/g) was achieved. The present study is successful in isolating a high yield multi enzyme producing A. foetidus strain and standardizing SSF parameters, which can be exploited industrially to achieve maximum enzyme yield.
Keywords: Aspergillus foetidus; Rice bran; Solid state fermentation; Wheat bran